DUAL PATHOLOGY IN THE BREAST: A RARE CASE REPORT OF PSEUDOANGIOMATOUS STROMAL HYPERPLASIA OVERLAPPING WITH INVASIVE DUCTAL CARCINOMA IN A POSTMENOPAUSAL FEMALE - Ezhilbharathi; Govardhan Kumar Pola; Sreedevi; Thanka Johnson (The Bioscan, 2026)
Pseudo-angiomatous Stromal Hyperplasia (PASH) is a benign myofibroblastic proliferation of the breast stroma. It is typically hormone-responsive and found more frequently in younger females. The coexistence of PASH with invasive ductal carcinoma in postmenopausal women is uncommon. This is a case of a 51-year-old postmenopausal female, presenting with a painful lump in the left breast. Both the clinical and radiological findings were suggestive of malignancy and the patient was planned for a modified radical mastectomy. The histopathological analysis revealed a dual pathology of invasive ductal carcinoma overlapping with PASH-like areas in the adjacent stroma. This case highlights the importance of accurate histopathological evaluation to differentiate PASH from malignant vascular tumors and to manage the underlying malignancy. Timely and accurate diagnosis of PASH might be helpful in prevention of unnecessary diagnostic and therapeutic interventions. Management of IDC preoperative, surgical and adjuvant therapy can address PASH alongside.